COMPREHENSIVE REVIEW OF MEDICAL RECORDS TECHNOLOGY AND ASSESSING SYSTEM INTEGRATION, DATA ACCURACY, AND COMPLIANCE WITH PRIVACY REGULATIONS FOR EFFECTIVE PATIENT RECORD MANAGEMENT - Majed Sagi Alharbi, Ayadmohsen Alotaibi, Mulhem Abdulah Alsubaie, Abdul Rahman Zaid Alrouji, Mohammed Abdullah Mohammed Alolyaani, Mohammed Abdullah AlthabitL, Abdullah Saeed Alsalem, (Chelonian Research Foundation, 2022)
Despite the fresh introduction of medical records technology, it has grown to be indispensable in our present-day healthcare systems, aiding in the storage and sharing of patient information. This thorough study takes a look at the integration of medical record systems, the reliability of data, and compliance with rules concerning privacy, among others, to be able to make proper decisions on the subject of patient record management. In this review, I will give an overview of what is currently being done, showcasing challenges and trends and aiming to deliver to you the very best practices to make health records technology-optimized healthcare for patients and healthcare providers. Keywords: electronic health records, computer-based technology, system integration, data accuracy, healthcare regulation and privacy rules, patient records management.